Usage Analysis of Mobile Payment System to Consumer Continuance Intention in Jabodetabek - Ankadhitra, Alif; Christiandy, Christiandy; Tamara, Dewi (International Journal Labs, 2023)
This research aims to study the continuous intention of mobile payment usage using the Technology Acceptance Model (TAM) theory with the extended model using perceived trust and subjective norms. A survey conducted through 25 questions questionnaire using a 5-point Likert scale with a total of 158 respondents was obtained by multiplying indicators by 6, with SEM-PLS method using SmartPLS 4.0. The analysis shows that perceived satisfaction significantly affects continuance intention to use mobile. The effect of subjective norms on continuance intention to use mobile payment is significant, and perceived ease of use and perceived usefulness have shown a positive relationship to perceived satisfaction. The perceived trust does not significantly affect the continuance intention to use mobile payment. In the previous study, continuance usage of mobile payment is conducted in South Africa, which is a gap in people's finances. The main limitation of this research is the limited data and a very diverse profile of respondents, which may have needed to be more fairly represented in this study. These results suggest that the mobile payment service provider effectively improves customer satisfaction. Gaining more trust in many aspects to make customers use mobile payment continuously. Perceived satisfaction has a positive relationship to keep the continuance intention to use mobile payment systems.